2004
DOI: 10.1111/j.1365-294x.2004.02153.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyandry and fitness in the western harvester ant,Pogonomyrmex occidentalis

Abstract: Using four highly polymorphic microsatellite markers (12-28 alleles), we gentoyped workers from 63 colonies of Pogonomyrmex occidentalis. Colonies have a single, multiply mated queen, and an average number of 6.3 patrilines per colony. Colony growth was measured over an 8-year period in the study population. Intracolonial relatedness and colony growth are correlated negatively, indicating a substantial fitness benefit to multiple mating.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
75
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(79 citation statements)
references
References 63 publications
2
75
1
1
Order By: Relevance
“…Genetic diversity was also shown to reduce colony-level variance in task performance or at maintaining a stable temperature in the nest (Jones et al 2004). In ants, increased genetic diversity is correlated with higher growth rates and survival of the colonies in the harvester ant, Pogonomyrmex occidentalis (Wiernasz et al 2004), but not with colony productivity in F. truncorum (Sundström & Ratnieks 1998) and Lasius niger . In a more causal study in which genetic diversity of colonies was experimentally manipulated, Rosset et al (2005) recently showed that increased genetic diversity had no significant impact on task efficiency (exploration of new territories, food collection, nest moving and corpse removal) and overall colony productivity in the Argentine ant, Linepithema humile.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity was also shown to reduce colony-level variance in task performance or at maintaining a stable temperature in the nest (Jones et al 2004). In ants, increased genetic diversity is correlated with higher growth rates and survival of the colonies in the harvester ant, Pogonomyrmex occidentalis (Wiernasz et al 2004), but not with colony productivity in F. truncorum (Sundström & Ratnieks 1998) and Lasius niger . In a more causal study in which genetic diversity of colonies was experimentally manipulated, Rosset et al (2005) recently showed that increased genetic diversity had no significant impact on task efficiency (exploration of new territories, food collection, nest moving and corpse removal) and overall colony productivity in the Argentine ant, Linepithema humile.…”
Section: Discussionmentioning
confidence: 99%
“…3), the associated P value (0.07) has marginal significance, indicating a higher mating frequency, sperm precedence, or extrinsic influences on colony founding success. Other harvester ant species, P. rugosus, Pogonomyrmex occidentalis, and Pogonomyrmex badius, show considerable variability in patriline numbers and an unequal patriline representation within colonies (11,35,36). Thus, even if a queen mates with multiple males, the sperm of a single male may be overrepresented during initial brood production.…”
Section: Discussionmentioning
confidence: 99%
“…parasites, pathogens). Increasing genetic diversity within colonies has been shown to enhance productivity and fitness in social insects (ants: Cole & Wiernasz 1999;Wiernasz et al 2004; honeybee, Apis mellifera: Tarpy Rueppell et al 2008). This hypothesis, however, seems, unlikely to account for the relationship between the number of mates and the contribution of queens to the brood.…”
Section: Discussionmentioning
confidence: 99%